Effectiveness of Public Service Malls in Depok City, West Java Province - Helviana Rahayu; Hyronimus Rowa; Ika Sartika (Sean Institute, 2025)
This study examines the effectiveness of the Public Service Mall (MPP) in Depok City, West Java Province, with a focus on its ability to provide efficient and easily accessible public services to the public. With the rapid development of digital technology, public expectations for more transparent, efficient, and user-friendly public services are increasing. MPP, as an integrated public service center, aims to meet this need by combining various government and private service providers in one place, thereby improving the quality of service. This study uses the theory of effectiveness developed by Steers (1985), focusing on three main dimensions: goal achievement, integration, and adaptation. This study uses a qualitative method with data collection techniques in the form of direct observation, interviews, and document analysis. The data analysis technique used is thematic analysis. This method is used to evaluate the extent to which MPP has succeeded in achieving its goals and identifying factors that hinder its effectiveness, and efforts to explore strategies to improve the efficiency of services provided at MPP Depok City. The results of the study indicate that although MPP is still ineffective in achieving its goals despite having made significant progress in streamlining public services. There are still challenges, especially in terms of organizational structure, coordination between agencies and digital literacy of the community. Recommendations are given to improve service integration, strengthen communication between agencies, and increase the use of digital tools to optimize services. These efforts are essential to ensure that MPP can meet the growing demands of the community and contribute to increasing the effectiveness of public services in Depok.